Effects of fragmentation of clones compound over vegetative generations in the floating plant Pistia stratiotes. (17th August 2020) - Adomako, Michael Opoku; Alpert, Peter; Du, Dao-Lin; Yu, Fei-Hai
Abstract: Background and Aims: Clonal plants dominate many plant communities, especially in aquatic systems, and clonality appears to promote invasiveness and to affect how diversity changes in response to disturbance and resource availability. Understanding how the special physiological and morphological properties of clonal growth lead to these ecological effects depends upon studying the long-term consequences of clonal growth properties across vegetative generations, but this has rarely been done. This study aimed to show how a key clonal property, physiological integration between connected ramets within clones, affects the response of clones to disturbance and resources in an aquatic, invasive, dominant species across multiple generations. Methods: Single, parental ramets of the floating stoloniferous plant Pistia stratiotes were grown for 3 weeks, during which they produced two or three generations of offspring; connections between new ramets were cut or left intact. Individual offspring were then used as parents in a second 3-week iteration that crossed fragmentation with previous fragmentation in the first iteration. A third iteration yielded eight treatment combinations, zero to three rounds of fragmentation at different times in the past. The experiment was run once at a high and once at a low level of nutrients. Results: In each iteration, fragmentation increased biomass of the parental ramet, decreased biomass of the offspring and increased number of offspring. These effects persisted and compounded from one iteration to another, though more recent fragmentation had stronger effects, and were stronger at the low than at the high nutrient level. Fragmentation did not affect net accumulation of mass by groups after one iteration but increased it after two iterations at low nutrients, and after three iterations at both nutrient levels. Conclusions: Both the positive and negative effects of fragmentation on clonal performance can compound and persist over time and can be stronger when resource levels are lower. Even when fragmentation has no short-term net effect on clonal performance, it can have a longer-term effect. In some cases, fragmentation may increase total accumulation of mass by a clone. The results provide the first demonstration of how physiological integration in clonal plants can affect fitness across generations and suggest that increased disturbance may promote invasion of introduced clonal species via effects on integration, perhaps especially at lower nutrient levels.